2022
DOI: 10.3389/fphys.2022.910568
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gastrointestinal Microbiota in Functional Dyspepsia: A Review

Abstract: Functional dyspepsia is a clinically common functional gastrointestinal disorder with a high prevalence, high impact and high consumption of medical resources. The microbiota in the gastrointestinal tract is a large number of families and is one of the most complex microbial reservoirs in the human body. An increasing number of studies have confirmed the close association between dysbiosis of the gastrointestinal microbiota and the occurrence and progression of functional dyspepsia. Therefore, we reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…However, a number of studies have revealed a strong association between FD with gastrointestinal motility and the intestinal microbiota. 49 Just as previous studies have demonstrated, the administration of LOP significantly reduced gut microbial richness and diversity compared to the CK group, 50 which was similar to the condition of FD patients. As a common drug used for the treatment of gastrointestinal dysmotility, although mosapride performed well in the relief of this symptom, it was not able to normalize microbiota richness and diversity in LOP-induced FD mice.…”
Section: Food and Function Papersupporting
confidence: 60%
“…However, a number of studies have revealed a strong association between FD with gastrointestinal motility and the intestinal microbiota. 49 Just as previous studies have demonstrated, the administration of LOP significantly reduced gut microbial richness and diversity compared to the CK group, 50 which was similar to the condition of FD patients. As a common drug used for the treatment of gastrointestinal dysmotility, although mosapride performed well in the relief of this symptom, it was not able to normalize microbiota richness and diversity in LOP-induced FD mice.…”
Section: Food and Function Papersupporting
confidence: 60%
“…361 FD pathogenesis is linked to GI dysmotility, visceral hypersensitivity, impaired gastric tolerance, disrupted gastrointestinal mucosal integrity, abnormal function of the gut microbiome−brain axis, increased eosinophils in duodenum, dysbiosis, Helicobacter-pylori infection, postgastrointestinal infection, diet, genetics, and mental and psychological factors. 278 An increasing number of studies have confirmed the close association between disturbance in the relative abundance and composition of the gastrointestinal microbiota and the occurrence and progression of FD. Actinomyces, Atopobium, Leptotrichia, Prevotella, and Veilonella counts differ between FD and control patients.…”
Section: ■ Gut Microbiome−brain Axismentioning
confidence: 98%
“…Furthermore, SCFAs, especially butyrate, provide more than 70% of the energy for the intestinal epithelial cells on top of their abilities to inhibit the multiplication and growth of pathogenic bacteria and the activity of intestinal inflammatory mediators, thus playing an anti-inflammatory role in the intestinal tract. 278 Lipid metabolites can affect intestinal permeability and intestinal immunity. The gut microbiota can produce lipopolysaccharides that could stimulate proinflammatory mediators, thereby disrupting the body's immune system and inducing local and systemic inflammatory responses.…”
Section: ■ Gut Microbiota Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations